Histological Study of Muscle Injuries to Observe the Effects of Environmental Pollutants on its Recovery and Regeneration (Medical Forum Monthly, 2024)
Objective: Humans are exposed to environmental pollution, food contamination and Cigarette smoking. Environmental pollution in addition to its effects on different systems of body, it also effect on recovery and regeneration of muscular injuries. In this study under different environments the recovery period and regeneration of muscular injuries will be studied on the basis of muscle histology.Study Design: Experimental study. place and Duration of Study: This study was conducted in Animal room of Anatomy Department, Postgraduate Medical Institute, Lahore from May 2011 to December 2011.Materials and Methods: Study was carried out on total "100" animals. Control group comprises 28 animals exposed to (i) "Blunt trauma ", (ii) Incisional injury., (iii) thermal injury and (iv) chemical injury. Whereas other nine groups of animals following initiation of injury were exposed to heavy metal pollutants and non-heavy metal pollutants by orally, parentally or inhalation. Delayed wound healing was observed, because major factors limiting the ability of skeletal muscles to regenerate after trauma or diseases were a viable population of satellites cells, re-innervation and re-vascularization.Results: The experimental group animals became more lethargic, inactive, death rate was more. Death occurred earlier in group " 6" & 8 as compared to rest of groups ( P < 0.01). Injured muscle initially showed increase in circumference and then followed by resuming its normal size in two weeks. time interval.Conclusion: In control group wound healing occurred in normal time whereas those exposed to metallic and non-metallic environmental pollutants showed weight reduction and delayed wound heating.